Hydrothermally altered deposits of 2014 Askja landslide, Iceland, identified by remote sensing imaging - Marzban, Pouria; Bredemeyer, Stefan; Walter, Thomas R.; Kästner, Friederike; Müller, Daniel; Chabrillat, Sabine (Frontiers in Earth Science, 2023)
Volcanic flanks subject to hydrothermal alteration become mechanically weak and gravitationally unstable, which may collapse and develop far-reaching landslides. The dynamics and pathways of the proximal part of volcanic landslides are barely preserved and challenging to determine, which is due to the steep slopes and the inherent instability. Here we analyze the proximal deposits of the July 21, 2014 landslide at Askja (Iceland), by combining high-resolution imagery from satellites and Unoccupied Aircraft Systems (UAS). We performed a Principal Component Analysis (PCA) in combination with supervised classification to identify different material classes and altered rocks. We trained a maximum-likelihood classifier and were able to distinguish 7 different material classes and compare these to ground-based hyperspectral measurements that we conducted on different rock types found in the field. Results underline that the northern part of the landslide source region is a hydrothermally altered material class, which bifurcates halfway downslope and then extends to the lake. We find that a large portion of this material is originating from a lava body at the landslide headwall, which is the site of intense hydrothermal activity. By comparing the classification result to in-situ hyperspectral measurements, we were able to further identify the involved types of rocks and the degree of hydrothermal alteration, and to discuss associated mechanical weakening. As the study demonstrates the success of our approach for identification of altered and less altered materials, important implications for hazard assessment in the Askja caldera and elsewhere can be drawn.